Schaum's ountline of theory and problems of heat transfer - Pitts, Donald R. (McGraw-Hill, 1998)
This book contain chapters:introduction; one-dimensional steady-state conduction; multidimensional steady-state conduction; time-varying conduction; fluid mechanics; forced convection; turbulent flow; natural convection; boiling and condendation; heat exchangers; radiation.